Substitution of a Surface-Exposed Residue Involved in an Allosteric Network Enhances Tryptophan Synthase Function in Cells - D’Amico, Rebecca N.; Bosken, Yuliana K.; O’Rourke, Kathleen F.; Murray, Alec M.; Admasu, Woudasie; Chang, Chia-en A.; Boehr, David D. (Frontiers in Molecular Biosciences, 2021)
Networks of noncovalent amino acid interactions propagate allosteric signals throughout proteins. Tryptophan synthase (TS) is an allosterically controlled bienzyme in which the indole product of the alpha subunit (aTS) is transferred through a 25 angstrom hydrophobic tunnel to the active site of the beta subunit (bTS). Previous nuclear magnetic resonance and molecular dynamics simulations identified allosteric networks in aTS important for its function. We show here that substitution of a distant, surface-exposed network residue in aTS enhances tryptophan production, not by activating aTS function, but through dynamically controlling the opening of the indole channel and stimulating bTS activity. While stimulation is modest, the substitution also enhances cell growth in a tryptophan-auxotrophic strain of Escherichia coli compared to complementation with wild-type aTS, emphasizing the biological importance of the network. Surface-exposed networks provide new opportunities in allosteric drug design and protein engineering, and hint at potential information conduits through which the functions of a metabolon or even larger proteome might be coordinated and regulated.